Phenotype and functions of human dendritic cells derived from CD14+ monocyte subsets opposed to CD16 expression - E. R. Chernykh; T. V. Tyrinova; O. Yu. Leplina; M. A. Tikhonova; Yu. D. Kurochkina; E. A. Oleynik; L. V. Sakhno; A. A. Ostanin (Бюллетень сибирской медицины)
The aim of the study was to analyze the relationship between monocyte subpopulations and phenotype/ functions of monocyte-derived dendritic cells (DCs), as well as DC sensitivity to the tolerogenic effect of dexamethasone.Materials and methods. The study included 15 healthy donors. DCs were generated by cultivating enriched fractions of CD14+ monocytes with or without CD16+cell depletion (CD16-Mo-DCs or CD16+Mo-DCs, respectively) in the presence of interferon alpha (IFNα) and granulocyte-macrophage colony-stimulating factor (GM-CSF). Monocyte subpopulations were obtained by immunomagnetic negative selection.Results. CD16+Mo-DCs were characterized by higher percentage of mature (CD83+CD14-) and lower number of semi-mature (CD14+CD83+) cells, but were similar to CD16-Mo-DCs by HLA-DR and CD86 expression, involved in the presentation of antigens and activation of naive T-cells. and also to co-inhibitory/ tolerogenic molecules B7-H1 and TLR-2. CD16+Mo-DCs displayed higher allostimulatory activity, which was positively correlated with CD86 expression (rS = 0.69; p = 0.027) and negatively – with TLR-2 expression (rS = -0.72; p = 0.1). Allostimulatory activity of CD16-Mo-DCs was positively correlated with the number of mature CD14-CD83+DCs and semi-mature CD14+CD83+DCs. Addition of dexamethasone (10-6 M) into CD16-Mo-DCs and CD16+Mo-DCs cultures led to the delay of DC maturation, the decrease of CD86 and the increase of TLR-2 expression, as well as the increase of cells with co-inhibitory CD86- B7-H1+ phenotype that was positively correlated with the reduction of DC allostimulatory activity. The decrease of CD86+/TLR-2+ index in CD16+Mo-DC population was due to the reduction of CD86+DCs and in CD16-Mo-DC population – to the increase of TLR-2+cells. Dexamethasone possessed higher inhibitory effect on DC maturation in the CD16+Mo-DC cultures.Conclusion. CD14+ monocytes, both contained and depleted by CD16+ cells, can differentiate into DCs when cultured with IFNα. The presence of CD16+ cells in whole blood monocyte pool is associated with generation of DCs showed a more mature phenotype and higher allostimulatory activity. Both CD16- and CD16+ monocyte-derived DCs are sensitive to suppressive effect of dexamethasone. However, dexamethasone tolerogenic effect involves different mechanisms in CD16-Mo-DCs and CD16+Mo-DCs.